GREEN ACCOUNTING DAN KINERJA LINGKUNGAN: STRATEGI MENYELAMATKAN BUMI ATAU MENGUNTUNGKAN DIRI SENDIRI? - Siti Nurlatifah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
ABSTRACT This study examines the effect of green accounting and environmental performance on the profitability of manufacturing companies in the consumer goods industry sector in Indonesia. The research data is in the form of annual financial reports for the period of 2018-2022 obtained from the official BEI website. The research sample consists of 60 data selected by purposive sampling. Data analysis uses multiple linear regression with SPSS for Windows version 26.0. The results show that green accounting has a negative and significant effect on profitability, while environmental performance has a positive and significant effect on profitability. This indicates that green accounting is not effective as a strategy to save the earth or benefit oneself, but rather causes high costs without providing significant added value. On the contrary, environmental performance is effective as a strategy to save the earth and benefit oneself, because it can increase resource efficiency, reduce environmental costs, meet consumer expectations, increase reputation, and strengthen the competitive advantage of the company. Green accounting and environmental performance together have a significant effect on profitability. This study provides implications for companies, governments, and society about the importance of green accounting and environmental performance in improving profitability and sustainability of the company.